Epidemiology foundations : the science of public health - Fos, Peter J. (Jossey-Bass, 2011)
"Epidemiology Foundations is an accessible introduction to epidemiology. This comprehensive resource covers the topic including information on its foundations, history, health and disease, descriptive epidemiology, measurement, study designs, uses, epidemics, social epidemiology, screening, community health, and global health. This book has been developed to closely respond to recommendations by the Consensus Conference on Undergraduate Public Health Education and is designed for use an introductory text for a course in epidemiology or in any class that features the topic epidemiology"--Provided by publisher.